Bogus transformations in mechanics of continua. (February 2016) - Pucci, Edvige; Saccomandi, Giuseppe; Vitolo, Raffaele
Abstract: In this paper we consider the structure of the symmetry group of some important mechanical theories (nonlinear elasticity and fluids of grade n ). We discuss why the invariance with respect to some well-known transformations must be used with care and we explain why some of these universal transformations are useless to obtain invariant solutions of physical significance.